Aspectos da paisagem cárstica do entorno do rio Azuis, Tocantins: caracterização geomorfológica e contribuições para gestão ambiental - Alves, Luiz Ricardo Ferreira (Universidade Federal do Tocantins, 2018)
River Azuis is neighbours one of the most speleological importance area in the state of Tocantins, and this name azuis blue is reference to crystalline waters and blue tones waters. Such characteristics are related by its location in a karst area. The karst landscapes are exposed, directly and indirectly, to the various human actions, resulting in its degradation, and being able to affect even beyond its limits. Thus, the objective of this work is to analyze the karstic landscape in the surroundings of the river Azuis, proposing reflections on its dynamics in the Physical-Social conjunction. The proposal of this research is identifying the dynamics in the landscape generated by the historical evolution of the occupation and the physical contextualization of the environment, as well as the production of a geomorphological map of karst with detailed scale (1: 25,000) to identify its features, seeking to understand the physical characteristics of the area from the triad materials - processes - forms, in addition to raising data for environmental diagnosis and management. In order to do so, fieldwork was carried out to analyze and describe the landscape, as it has been transformed by human actions and its active processes, as well as the application of semi-structured interviews to local residents. Many karstic features were identified, exposed to various human actions, compromising their natural dynamics. Numerous problems were found regarding the absence of environmental management, not only due to the presence of tourist activity, but also several other activities, and based on the perception of the residents, the landscape suffered and still suffers from numerous changes that affect the Azuis and the karst system in general. It is necessary to implement a Management Plan that addresses all the care related to environmental issues covered by environmental legislation, alongside the supervision of the responsible agencies. The geomorphological map of the karst provided a detailed analysis of the elements of the relief, prioritizing its structural features, which made it possible to describe the active processes. Therefore, it is an area that presents great speleological, geomorphological and tourist potentialities, as well as providing numerous future study possibilities in the context of Physical Geography, not only the municipality of Aurora do Tocantins, but the entire southeastern region of the State of Tocantins.